THE EFFECT OF BRAND EXPERIENCE ON BRAND TRUST AND BRAND LOYALTY - Didit Darmawan (Universitas Islam Balitar, 2018)
The marketing literature has acknowledged that consumers are looking for brands that provide a good, unique and unforgettable experience. The success of a brand in the long run depends greatly on the number of loyal consumers who regularly buy on a particular brand. This study aims to analyze and discuss the effect of brand experience on brand trust and brand loyalty. The research method used is a survey. The population in this study were consumers of Zwitsal products as a product for babies but used among adults. Respondents were set at 100 people. The sampling method used in this study is a non probability sampling method. The technique used is convenience sampling where respondents are based on anyone who by chance is seen as fulfilling the requirements as a data source. The analytical tool used is linear regression with the help of SPSS 24.0 for Windows software. The results show that brand experience has a significant positive effect on brand trust, and brand experience has a significant positive effect on brand loyalty